1983
DOI: 10.1099/00221287-129-6-1743
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Classification of Streptomyces and Related Genera

Abstract: Four hundred and seventy-five strains, which included 394 type cultures of Streptomyces and representatives of 14 other actinomycete genera, were studied. Overall similarities of these strains for 139 unit characters were determined by the SSM and SJ coefficients and clustering by the UPGMA algorithm. Test error and overlap between the phena defined were within acceptable limits. Cluster-groups were defined by the SSM coefficient at the 70.1% similarity (S) level and by the SJ coefficient at the 50% S-level. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
994
0
11

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 918 publications
(1,035 citation statements)
references
References 89 publications
30
994
0
11
Order By: Relevance
“…were described (461). By 1970, the total had increased to 3,100, although many species had been inadequately described or cited in patent literature (592 (638,640) suggested that the significant weighting given to morphologic characters in prior classifications was no longer justified. They suggested that there should be relatively few cluster groups (or species) within the genus and assigned over 300 Streptomyces and Streptoverticillium spp.…”
Section: Opportunistic Pathogenic Actinomycetesmentioning
confidence: 99%
“…were described (461). By 1970, the total had increased to 3,100, although many species had been inadequately described or cited in patent literature (592 (638,640) suggested that the significant weighting given to morphologic characters in prior classifications was no longer justified. They suggested that there should be relatively few cluster groups (or species) within the genus and assigned over 300 Streptomyces and Streptoverticillium spp.…”
Section: Opportunistic Pathogenic Actinomycetesmentioning
confidence: 99%
“…The representative isolates and type strains of the three Agrococcus species studied were examined for a range of phenotypic properties using standard procedures: acid production from sugars (Hugh & Leifson, 1953); catalase activity, degradation tests and growth on organic acids as sole carbon sources (Gordon & Mihm, 1957, 1962; aesculin hydrolysis (Williams et al, 1983); allantoin and urea hydrolysis (Cowan, 1974); nitrate reduction and hydrogen sulphide production (Gordon, 1968); degradation of Tweens (Sierra, 1957); and the breakdown of glycerol tributyrate using tributyrin agar (Sigma). All tests were incubated at 30 uC for 14 days.…”
mentioning
confidence: 99%
“…Species under Streptomyces were first identified for their antibiotic production, which lead to overspeciation in the taxon, from an initial number of 40 species to more than 3000. Only after the launching of the International Streptomyces Project (ISP) which introduced keys identification criteria based on morphological aspect and numerical taxonomy by Williams et al, (1983) was this overspeciation limited and redescription of more than 450 species was done (Annaliesa and Wellington, 2001). Attention to nitrogen fixation among actinobacteria was focused only on genus Frankia, which are able to make symbiotic relationships with a range of actinorhizal plants (Benson and Silvester, 1993).…”
Section: Actinobacteria: Taxonomy and Propertiesmentioning
confidence: 99%